Efektivitas Air Perasan Daun Pandan Wangi Dalam Pengendalian Vektor Lalat Rumah (Musca Domestica) - Yunicho Yunicho; Andi Sry Wahyuni; Pratiwi Adam (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
Musca domestica is a type of fly species known as a carrier of disease and can be found in places where there is wet household waste, especially those rich in easily decomposed organic matter. The habit of flies looking for food and breeding in trash cans causes various disease-causing microorganisms to stick to the fly's feet and fine hairs all over the fly's body. The purpose of this study was to determine the effectiveness of fragrant pandan leaf concentrations of 50%, 70%, and 90% in killing house flies (Musca domestica). This research is experimental research with a posttest-only design with a control group. The sampling technique was carried out by purposive sampling. The results of this study indicated that the lowest average mortality of Musca domestica was found at a concentration of 50% in 15 individuals and the highest mortality was found at a concentration of 90% in 30 individuals. The higher the concentration of fragrant pandan leaf juice, the more effective it is in killing house flies (Musca domestica). The community can use the aromatic pandan leaf solution as an environmentally friendly plant insecticide.